2013
DOI: 10.1017/jfm.2013.575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluctuating energy input on the small scales in turbulence

Abstract: In the standard cascade picture of 3D turbulent fluid flows, energy is input at a constant rate at large scales. Energy is then transferred to smaller scales by an intermittent process that has been the focus of a vast literature. However, the energy input at large scales is not constant in most real turbulent flows. We explore the signatures of these fluctuations of large scale energy input on small scale turbulence statistics. Measurements were made in a flow between oscillating grids, with R λ up to 271, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…In presence of cores, exponent values for the power law varied from 0.58 to 1.83, averaging at 1.08 (Table ), thus deviating by 8% from the exponent of 1 found by Hopfinger and Toly () in an empty tank, without cores. Deviation from the exponent of 1 is likely due to the turbulence intermittency produced by unsteady vortex shedding in the near grid field (Chien et al ) as the power law fitting was performed closer from grid mid‐position (between 0.5 and 1.5 mesh size, due to the constrained space between grid and cores) than in previous experimental studies (Hannoun and List ; Redondo ; Fernando ) which validated the exponent of 1 beyond at least one mesh size away from the grid. Spatial heterogeneity of the flow statistics due to turbulence intermittency within or between cores was estimated by the residual error of the power law fitting and averaged at 16% for motor frequencies ranging from 0.5 Hz to 3.5 Hz among the four profiles.…”
Section: Assessmentmentioning
confidence: 77%
“…In presence of cores, exponent values for the power law varied from 0.58 to 1.83, averaging at 1.08 (Table ), thus deviating by 8% from the exponent of 1 found by Hopfinger and Toly () in an empty tank, without cores. Deviation from the exponent of 1 is likely due to the turbulence intermittency produced by unsteady vortex shedding in the near grid field (Chien et al ) as the power law fitting was performed closer from grid mid‐position (between 0.5 and 1.5 mesh size, due to the constrained space between grid and cores) than in previous experimental studies (Hannoun and List ; Redondo ; Fernando ) which validated the exponent of 1 beyond at least one mesh size away from the grid. Spatial heterogeneity of the flow statistics due to turbulence intermittency within or between cores was estimated by the residual error of the power law fitting and averaged at 16% for motor frequencies ranging from 0.5 Hz to 3.5 Hz among the four profiles.…”
Section: Assessmentmentioning
confidence: 77%
“…Their variations also become important only for large amplitude ratios. A recent related study of a similar effect can be found in [19]. They exploited experimentally the idea by Monin and Yaglom [20], section 25.1, who introduced a model to illustrate the influence of a fluctuating dissipation rate, or energy injection rate, on the Kolmogorov constant.…”
Section: Discussionmentioning
confidence: 98%
“…In the inertial range, 1 D LL = C 2 ( r) 2/3 , where C 2 ≈ 2.13 is expected to be a universal constant, although with some uncertainty. [23][24][25] Thus, the dissipation rate is often estimated in experiments by measuring D LL and scaling it appropriately. In Fig.…”
Section: B 3d Turbulencementioning
confidence: 99%